Dorsal Anterior Cingulate Cortex: A Role in Reward-Based Decision Making - Bush, George; Vogt, Brent A.; Holmes, Jennifer; Dale, Anders M.; Greve, Douglas; Jenike, Michael A.; Rosen, Bruce R. (Proceedings of the National Academy of Sciences - PNAS, 2002)
Dorsal anterior cingulate cortex (dACC) is a brain region that subserves cognition and motor control, but the mechanisms of these functions remain unknown. Human neuroimaging and monkey electrophysiology studies have provided valuable insights, but it has been difficult to link the two literatures. Based on monkey single-unit recordings, we hypothesized that human dACC is comprised of a mixture of functionally distinct cells that variously anticipate and detect targets, indicate novelty, influence motor responses, encode reward values, and signal errors. As an initial test of this conceptualization, the current event-related functional MRI study used a reward-based decision-making task to isolate responses from a subpopulation of dACC cells sensitive to reward reduction. As predicted, seven of eight subjects showed significant (P < 10-4) dACC activation when contrasting reduced reward (REDrew) trials to fixation (FIX). Confirmatory group analyses then corroborated the predicted ordinal relationships of functional MRI activation expected during each trial type (REDrew > SWITCH > CONrew ≥ FIX). The data support a role for dACC in reward-based decision making, and by linking the human and monkey literatures, provide initial support for the existence of heterogeneity within dACC. These findings should be of interest to those studying reward, cognition, emotion, motivation, and motor control.